식용 및 약용버섯의 항산화 및 In vitro 항암 효과 - 치용카이(Yongcai Qi); 조흔(Xin Zhao); 임양이(Yaung-Iee Lim); 박건영(Kun-Young Park) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2013)
The antioxidant and anticancer effects of the edible mushrooms Lentinus edodes (LE, Pyogo mushroom) and Agaricus blazei (AB, Agaricus mushroom), and the medicinal mushrooms Cordyceps militaris (CM, Dong chunghacho), Ganoderma lucidum (GL, Youngji mushroom), Inonotus obliquus (IO, Chaga mushroom), and Phellinus linteus (PL, Sangwhang mushroom) were studied in vitro. The bioactive components were extracted by methanol. The antioxidant effects were evaluated using the DPPH and hydroxyl radical scavenging assays. The antioxidant activities of medicinal mushrooms (35~90%) were higher than edible mushrooms (4~23%). The in vitro anticancer effects of the mushrooms were evaluated using the MTT assay in AGS gastric adenocarcinoma cells, HCT-116 colon carcinoma cells, and HepG2 hepatoma cells. The medicinal mushrooms CM, GL, IO, and PL showed 28~91% inhibition, while the edible mushrooms LE and AB exhibited 5~40% inhibition. The medicinal mushrooms, compared to edible mushrooms, effectively down-regulated the gene expression of the anti-apoptosis related gene Bcl-2 and inflammation-related genes iNOS and COX-2, and up-regulated the pro-apoptosis gene Bax (p<0.05). Total polyphenol and flavonoids contents of the medicinal mushrooms were 9.1~35.7 mg/g, while the edible mushrooms showed 0~13.3 mg/g. This study showed that antioxidant activities and anticancer activities in vitro increased in the order LE, AB, GL, CM, IO and PL. LE and AB showed the lowest effects among the samples, GL and CM had medium effects, and IO and PL exhibited the highest effects in the antioxidant and anticancer effect for three different human cancer cells. Taken together, PL resulted in the highest and LE the lowest effects in this study. 식용버섯(표고버섯과 아가리쿠스버섯)과 약용버섯(영지버섯, 동충하초, 차가버섯, 상황버섯) 추출물의 항산화효과와 인체 암세포(AGS, HCT-116, 및 HepG2) 성장 저해율, apoptosis 유도에 관련된 Bcl-2, Bax 유전자, 그리고 염증에 관련된 iNOS 및 COX-2 유전자의 분석을 통해 식용버섯과 약용버섯의 in vitro 항암효과를 비교하였다. DPPH와 hydroxy radical($OH{·}$) 소거능력은 표고버섯, 아가리쿠스버섯, 동충하초, 영지버섯, 차가버섯, 상황버섯 순으로 높았으며, 식용버섯보다는 약용버섯의 항산화효과가 더 높았고, 약용버섯 중 차가버섯과 상황버섯의 항산화효과는 78%와 90%로 상황버섯이 가장 우수하였다(p<0.05). AGS 위암세포, HCT-116 결장암세포, HepG2 간암세포에 대한 억제효과는 식용버섯인 아가리쿠스버섯과 표고버섯 추출물은 5~40%, 약용버섯인 영지버섯과 동충하초 추출물은 28~79%, 상황버섯과 차가버섯 추출물은 75~91%로 나타났다. Apoptosis 유도에 관련된 Bcl-2 및 Bax 유전자 발현과 염증에 관련된 iNOS 및 COX-2 유전자 발현은 표고버섯, 아가리쿠스버섯, 동충하초, 영지버섯, 차가버섯, 상황버섯 순으로 apoptosis를 유도하는 작용과 세포의 발암(염증) 유도과정을 억제하는 효과가 높게 나타났다. 총 폴리페놀과 플라보노이드 화합물의 함량은 상황버섯의 폴리페놀과 플라보노이드함량이 각각 317.2 mg/g 및 35.7 mg/g으로 가장 높게 나타났으며 차가버섯, 영지버섯, 동충하초, 아가리쿠스버섯, 표고버섯 추출물 순으로 함량이 낮아졌다. 식용버섯보다 약용버섯의 총 폴리페놀과 플라보노이드 화합물의 함유량이 많았고, 이들 화합물 함량이 많을수록 항산화효과와 인체 암세포의 성장 억제효과가 높아졌다.